Kelayakan E-magazine pada Submateri Keanekaragaman Hayati Indonesia kelas X SMA Berbasis Etnobotani Tumbuhan Obat Penyakit Hipertensi - Ramadhaniah, Putri Shaumi; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
The development of contextual, engaging, and technologically advanced learning media is essential to support the learning process. One innovation that can be implemented is the development of an e-magazine based on the ethnobotany of medicinal plants for hypertension. It is believed that an e-magazine featuring local potential expands students' understanding of biodiversity in their surroundings. An e-magazine is a digital learning medium packaged in an attractive, interactive, and easily accessible electronic magazine format via technological devices. The e-magazine medium enables students to learn independently at their own pace and according to their individual abilities. This study aims to analyze the feasibility of an e-magazine on the biodiversity of Indonesia for 10th-grade high school students, focusing on the local potential of Karangan Village, Landak Regency, and featuring ethnobotanical knowledge about the use of medicinal plants for hypertension. The method used was quantitative descriptive with several stages, namely the compilation of the e-magazine, validation of the e-magazine, and analysis of the validation results. The validation process was conducted by five experts, comprising biology teachers and biology education lecturers, evaluating language, content, and graphic aspects using a validation form. The research results showed that the e-magazine achieved a Content Validity Ratio (CVR) of 1 and a Content Validity Index (CVI) of 1, indicating that the e-magazine is valid and suitable for use as an alternative learning medium for biology in 10th-grade high school.